Upaya Hukum Terhadap Pemanggilan Notaris Yang Tidak Memenuhi Pasal 66 Ayat (1) UUJNP - Sisca Anindya Rachmawati (Faculty of Law Universitas Islam Indonesia, 2022)
The issue in this writing is how to take legal action against summons for a notary who does not comply with Article 66 paragraph (1) UUNJP and what crimes are related to the profession and position of a notary. The method of this research is normative or doctrinal in which the object is statutory regulations with a case or doctrine approach, then the primary legal material is statutory regulations and secondary legal material is in the form of books. The results of this study conclude that legal remedies taken by a notary against summons that do not comply with Article 66 paragraph (1) UUJNP are through pretrial since it has the authority to decide whether or not an arrest and or detention is legal at the request of the suspect or his family or other parties on the power of the suspect and that criminal acts related to the profession and position of a notary in the Criminal Code are Articles 263-266 as well as Articles 372 and 378, these articles indicate the involvement of the profession and position of a notary. Meanwhile, the author's suggestion is that investigators and public prosecutors should pay attention to other regulations apart from the Criminal Code and the Criminal Procedure Code so that no suspect's rights are overlooked and for a notary to always act in professional manner and being thorough or prudent in formulating a deed.Key Word: Legal Remedies, Summons, Notary AbstrakPermasalahan dalam penulisan ini adalah bagaimana upaya hukum terhadap pemanggilan notaris yang tidak memenuhi Pasal 66 ayat (1) UUNJP dan tindak pidana apa saja yang berhubungan dengan profesi dan jabatan notaris. Dan metode penelitian ini adalah normatif atau doktrinal yang objeknya adalah peraturan perundang-undangan dengan pendekatan kasus maupun doktrin kemudian bahan hukum primer adalah peraturan perundang-undangan dan bahan hukum sekunder ialah berupa buku. Hasil penelitian ini menyimpulkan bahwa upaya hukum yang dilakukan seorang notaris terhadap pemanggilan yang tidak memenuhi Pasal 66 ayat (1) UUJNP adalah melalui praperadilan sebab praperadilan berwenang memutus sah atau tidaknya suatu penangkapan dan atau penahanan atas permintaan tersangka atau keluarganya atau pihak lain atas kuasa tersangka dan bahwa tindakan pidana yang berhubungan dengan profesi dan jabatan notaris dalam KUH Pidana adalah Pasal 263-266 maupun Pasal 372 dan 378, pasal-pasal tersebut berindikasi melibatkan profesi dan jabatan notaris. Sedangkan saran penulis adalah penyidik dan penuntut umum agar memperhatikan peraturan lain selain dari KUH Pidana maupun KUH Acara Pidana agar tidak ada hak-hak tersangka yang terlewatkan dan bagi notaris adalah agar selalu bersikap profesional dan saksama atau kehati-hatian dalam setiap pembuatan akta.Kata-kata Kunci: Upaya Hukum, Pemanggilan, Notaris